Evaluación de tres dosis de harina de cáscara de camarón como alternativa proteica en la etapa de crecimiento en cerdos raza pietrain - Pacheco Benavides, Carlos Alfredo (2024)
Today there is a wide variety of concentrated feeds and various products for pig nutrition that are distributed and marketed. Shrimp shell meal is not effectively utilized as a protein source in diets for growing and fattening pigs, despite its nutritional benefits for these animals. The objectives set were: 1) Evaluate the productive behavior of pigs in the growth stage, supplemented with three doses of shrimp shell meal. 2) Determine the optimal level of shrimp shell meal in the diet of pigs in the growth stage. 3) Establish the benefit/cost relationship of using shrimp shell meal in the growth stage. The research was carried out at the Laguacoto I Experimental Farm, Guaranda canton, where a DBCA was carried out with 4 treatments and 3 repetitions. In the results it can be seen that the highest weight at the end of the research was 62.67 kg in T3 (6% shrimp shell meal), in relation to the feed conversion it is observed that the highest average was T2 (Shrimp meal shrimp shell at 4%) with 3.78 kg, a benefit/cost ratio of T4 was also developed with 0.89 $, in none of the treatments with the addition of shrimp shell flour will profits be obtained. The results of this study clearly indicate that the inclusion of shrimp shell meal in their diet is not a determining element for the increase in their body weight.